Experimental Analysis Study Wave Drift Force of Moored Floating Production Units (FPU) - Rifliansah, Arifin; Nugroho, Wibowo Harso (Makara Journal of Technology, 2024)
Drift forces caused by sea waves and currents are an important aspect that needs to be studied in planning moored floating structures, especially Floating Production Units (FPU) type ships which are operated for oil and gas exploration. This study describes the drift forces on the FPU which is subjected to environmental loads in the form of waves. The slow-drift movement that occurs in a moored FPU, and experiencing irregular waves is a very important problem. The complexity of determining drift forces analytically and numerically requires the use of hydrodynamics model test. In the model test on a certain model scale the ship is equipped with several measuring instruments for measuring ship movement and the forces acting on the mooring lines. The Model testing was also carried out by providing a simulation of environmental forces in the form of currents and ocean waves which were varied in several wave headings. The magnitude of the mean wave drift force that occurs on FPU is very dependent on the heading angle of the wave excitation and current as well as the significant wave height and peak frequency.